Mobile Bearing Total Knee Arthroplasty for Valgus Knee Osteoarthritis with Permanent Patellar Dislocation: A Case Report and Review of the Literature - Kohei Kamada; Tomoyuki Matsumoto; Koji Takayama; Daisuke Araki; Shingo Hashimoto; Shinya Hayashi; Takehiko Matsushita; Ryosuke Kuroda (Case Reports in Orthopedics)
Permanent patellar dislocation with tibiofemoral joint osteoarthritis is a relatively rare condition. To treat this condition, total knee arthroplasty with proximal or distal realignment of the extensor mechanism has been reported. We report a challenging case of an 80-year-old woman diagnosed with permanent patellar dislocation with tibiofemoral joint osteoarthritis treated by a mobile bearing total knee arthroplasty utilizing navigation system. Lateral retinaculum release was performed to improve patellar tracking; other proximal or distal realignment of the extensor mechanism was not necessary. Postoperative radiographs show stable patellar tracking and recurrent patellar dislocation was not observed. This clinical case indicates that the implant’s precise alignment and rotation during total knee arthroplasty could settle anatomical abnormalities of permanent patellar dislocation and the mobile bearing insert could contribute to stabilizing patellar tracking.